Avaliação da autodepuração do Rio Tambay na cidade de Bayeux Paraíba/Brasil - Falcão, Jakeliny Costa (2011)
The water is usually classified as a renewable natural resource in quantity but not quality. The quality and quantity of it, will depend on how the man uses, but it is known that the man often uses this resource in an inappropriate way, causing often irreversible damage. The Tambay river is located in the city of Bayeux, state of Paraiba - Brazil, used in some places as municipal boundary between the towns of Bayeux and Santa Rita, with its river mouth located in the town of Bayeux in Paroeiras river and its source in the same town in the district of Alto da Boa Vista. This river has a length of approximately 3.51 km from the mouth to the source. Nearby its mouth river there is the dam of Santo Amaro, which years ago had breached its spillway and now appear as two distinct bodies of water. Water pollution originates from various sources, among which stand out domestic effluent, industrial effluents, the urban and agricultural runoff surface and is therefore associated with the use type and land occupation. It was observed that the population living around the basin using the river water for different uses such as irrigation, watering the animals, eviction of effluents, solid waste disposal, recreation, among others. To perform the research, some parameters were analyzed: pH, turbidity, color, total dissolved solids, nitrite, nitrate, dissolved oxygen, biochemical oxygen demand and thermotolerant coliform. The results of this analysis were compared with the values allowed by the CONAMA Resolution number 357/2005, to Class II river. It is observed that the parameters nitrite, nitrate, dissolved oxygen, biochemical oxygen demand, thermotolerant coliform, behaved mostly above those permitted by the above resolution. Organic pollution of a watercourse can be evaluated by the decrease in dissolved oxygen concentration and / or the concentration of organic matter in terms of concentration of oxygen needed to oxidize it. Dissolved oxygen (DO), biochemical oxygen demand (BOD) and thermotolerants coliforms were used as parameters to evaluate the self-purification of Tambay river. Evaluations were made of organic pollution profile through water sampling conducted over a period of one year and five months and were identified the areas of self-purification, over the course of the river, where it was possible to correlate DO with the BOD, but according with the results, Tambay river is in poor condition, silted, very polluted and unable to self-purify.